Evolution of Educational Commission for Foreign Medical Graduates Certification in the Absence of the USMLE Step 2 Clinical Skills Examination. (25th October 2022) - Mladenovic, Jeanette; van Zanten, Marta; Pinsky, William W.
Abstract : The United States Medical Licensing Examination Step 2 Clinical Skills (CS) was paused in 2020 because of the ongoing COVID-19 pandemic and discontinued in 2021. Step 2 CS was an important tool to assess readiness of international medical graduates (IMGs) to enter graduate medical education (GME) in the United States. This article describes the Educational Commission for Foreign Medical Graduates' (ECFMG's) response to the discontinuation of Step 2 CS. ECFMG certifies IMGs who seek eligibility for GME and licensure in the United States. Requirements for ECFMG certification include, among other factors, demonstration of adequate clinical skills and English proficiency, which were previously assessed as part of Step 2 CS. Beginning in June 2020 and during the next year, ECFMG modified the certification process with the introduction of 6 opportunities (pathways) for IMGs to demonstrate adequate clinical skills and a new test of English proficiency. In addition, permanent ECFMG certification is now granted only after the successful completion of the first year of residency, as determined by the program director. The COVID-19 pandemic and discontinuation of Step 2 CS caused a significant crisis for many IMGs who sought entrance into the United States, impacting the careers of those who had planned entry and those who would be eligible for U.S. training and the future workforce. Despite challenges due to the ongoing global pandemic, ECFMG certification continues to allow qualified physicians to enter U.S. GME and ensures that these individuals are ready to begin supervised training.